STUDY OF EFFICIENCY OF GUDUCHI PRATAN (TINOSPORA CORDIFOLIA TENDRILS) AS HERBAL SUTURE MATERIAL IN TWAK SIVAN KARMA - *Yogesh Dnyandeo Narkhede; S.V. Kashikar (International Journal of Ayurveda and Pharma Research, 2015)
Wounds are the commonest problem faced by surgeon. Good approximation with good post-operative healing is the main aim of suturing of such wounds. Therefore many advancements in suture materials are done and being done in suture materials. Considering description in Ayurvedic texts like Surshrut Samhita, we can say that Sushruta has described various suture materials in detail. Also Sushruta has described proper techniques of suturing in detail. Modern suture materials are useful in todays era, but when we go through suture materials described by Sushruta, all are of natural origin. When we see towards modern suture materials, many of these are also from natural origin like intestine of goat, jute fibers etc. So considering these points a suture material described by Sushruta- Guduchi pratan was taken for study in view of testing its efficiency and whether it exhibits any medicinal property to wound. For these study effects were compared with Linen as this is also a poly filament suture material. Total 60 patients 30 in each group were taken for study and efficiency of both suture materials were assessed with criteria like Edema, Color, Temperature, Tenderness, and Discharge. Efficiency of Guduchi Pratan was found equal to Linen with extra benefit of faster wound healing due to anti-inflammatory and antibacterial property of Guduchi.